2020
DOI: 10.1038/s41598-020-59397-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecular real-time deep sequencing reveals the dynamics of multi-drug resistant haplotypes and structural variations in the hepatitis C virus genome

Abstract: While direct-acting antivirals (DAAs) for hepatitis c virus (HcV) have dramatically progressed, patients still suffer from treatment failures. For the radical eradication of HCV, a deeper understanding of multiple resistance-associated substitutions (RASs) at the single-clone level is essential. To understand HcV quasispecies and their dynamics during DAA treatment, we applied single-molecule real-time (SMRT) deep sequencing on sera from 12 patients with genotype-1b HCV infections with DAA treatment failures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…CCSs with a pass number of ≥5 were not only close to the best results of gap correction ( Fig. 2 ) but also revealed a low substitute error of ∼0.023% ( 36 ). Under this threshold, the SMRT platform produced an average of ∼20,000 qualified CCSs for each sample.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…CCSs with a pass number of ≥5 were not only close to the best results of gap correction ( Fig. 2 ) but also revealed a low substitute error of ∼0.023% ( 36 ). Under this threshold, the SMRT platform produced an average of ∼20,000 qualified CCSs for each sample.…”
Section: Discussionsupporting
confidence: 64%
“…The clone (or haplotype) number was much more than that produced from traditional Sanger methods, such as the study of SARS-CoV quasispecies that obtained 28 full spike clones for 19 patients ( 37 ). Under the same SMRT platform and threshold (pass number ≥ 5), a recent study of HCV quasispecies produced an average 8,130 CCSs for each sample ( 36 ). These indicated that a sufficient and high-quality data set was obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intra-host viral structural variants have also begun to be classified, opening up a new component of virus diversity to be explored (e.g. hepatitis C virus, Yamashita et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained an average 27,000 quasispecies sequences for each sample, and the number was more than the SARS-Cov quasispecies study using traditional sanger methods (28 spike sequences from 19 patients) 28 and results from the recent HCV quasispecies study using the same SMRT platform (average 8,130 CCS for each samples with pass > 5) 29 . More than 80,000 cumulative SNVs facilitated us to calculate the evolutionary rate at quasispecies level.…”
Section: Discussionmentioning
confidence: 99%